Marker assisted selection in Rasa Aragonesa sheep breed by using a SNP panel for parentage assignment - Lakhssassi K.; Iguacel L.P.; Sarto M.P.; Lahoz B.; Folch J.; Jiménez M.A.; Alabart J.L.; Serrano M.; Calvo J.H. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Accurate pedigree information is an essential tool in genetic breeding programs to ensure the highest rate of genetic gain and allow the management of inbreeding. In this sense, a panel of 192 SNPs, that included 153 SNPs for parentage assignment and 39 functional SNPs, is being used in the selection program for prolificacy of the Cooperative Oviaragon-Grupo Pastores in Rasa Aragonesa. Preselection of some young rams before entering progeny testing is being performed using some of the functional SNPs. For example, the FecXR allele of the BMP15 associated to increased prolificacy, and the PrnP genotypes related to scrapie susceptibility. Recently, four SNPs of the MNTR1A and LEPR genes associated to seasonality traits in Rasa Aragonesa have been included in the panel of 192 SNPs. Because of the increasing demand for hormone-free products and the evolution of European rules and directives towards a reduction, even a complete cessation of use of exogenous hormones leads to search for alternative methods such as the use of genetic markers which would be a powerful tool in selection programs. Therefore, the first objective of this research was to assess how to select some new SNPs for this SNP custom panel. Secondly, this research also aims to validate some putative causal SNPs using the SNP panel as a proof of concept.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)